2012
DOI: 10.1002/ijc.27567
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of polymorphisms in ABCB1, ABCC2 and ABCG2 and lung cancer chemotherapy response and prognosis

Abstract: ATP-binding cassette (ABC) transporter expression and genetic heterogeneity have been implicated in response to anticancer therapy. This study characterized genetic variability of the ABCB1 (also known as MDR1), ABCC2 (MRP2) and ABCG2 (BCRP) genes, which are key players in the metabolism of many chemotherapeutic agents including those used in the treatment of lung cancer. We genotyped 53 polymorphisms in the candidate genes in genomic DNA samples of 171 cases of small cell lung carcinoma (SCLC) and 206 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 50 publications
(101 reference statements)
3
39
1
Order By: Relevance
“…P-gp is encoded by ABCB1 and is considered to mediate MDR by reducing the intracellular accumulation of cytotoxic drugs and compounds. Many types of cancers express high ABCB1 levels and are unresponsive to chemotherapy (43,44); ABCB1 expression has been considered a predictor of poor response to chemotherapy and overall survival (45,46). Our results also indicated that UCUB cells with high expression of CEBPD are strongly resistant to CDDP and paclitaxel because of ABCC2 and ABCB1 activation (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…P-gp is encoded by ABCB1 and is considered to mediate MDR by reducing the intracellular accumulation of cytotoxic drugs and compounds. Many types of cancers express high ABCB1 levels and are unresponsive to chemotherapy (43,44); ABCB1 expression has been considered a predictor of poor response to chemotherapy and overall survival (45,46). Our results also indicated that UCUB cells with high expression of CEBPD are strongly resistant to CDDP and paclitaxel because of ABCC2 and ABCB1 activation (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…These results indicated that the ABCC2 genetic variation is an important factor in survival after chemotherapy in SCLC. 33 Although not all the patients in that study were treated with platinum-based chemotherapy, the results were similar to our own in that there was not a significant association between the genotype of SNP rs3109823 in ABCG2 and clinical outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…ABCC2 was moderately or highly upregulated in 16HBE, A549, L-132, H460, and H727 cells compared with other cell types and lung tissues. In tumor cell lines, ABCC2 mRNA overexpression was associated with resistance to multiple classes of anticancer drugs (Campa et al, 2012). Regarding the ABCC6 and ABCC9 genes, although they were moderately expressed in lung tissues, we failed to detect their mRNAs in most lung cell models.…”
Section: Number Of Genes Differentially Expressed Between Lung Cell Mmentioning
confidence: 76%